Liquefying a Market: The Transition of LNG to a Traded Commodity. Issue 1 (6th April 2017) - Pirrong, Craig
Abstract : The Liquefied Natural Gas (LNG) industry has grown significantly since it began a half‐century ago, and it will continue to diversify both its sources of supply and the contractual arrangements between suppliers and users. Economic theory says that contracting modes adapt to facilitate gains in efficiency, and that this process of adaptation responds to changes in technological, market, and regulatory factors. When an industry relies heavily on highly specialized assets with limited alternative uses, as is true of LNG, the use of longterm contracts (or vertical integration) will generally be more efficient than short‐term dealings. But once conditions begin to encourage vigorous competition among buyers and sellers, it becomes increasingly economical to rely on shorter‐term (and spot) markets for exchange. The history of the LNG industry supports these theoretical predictions, and illustrates the transition from one contracting mode to another. For most of its history, the specialization and scale of LNG assets dictated the predominant use of long‐term contracting. In recent years, however, market and regulatory changes have raised the demand for short‐term and spot contracting, which in turn has provided the impetus for a virtuous cycle of market liquidity. As buyers and sellers have become increasingly able to obtain or dispose of LNG in an active market, they have needed less protection against the opportunism of trading partners that long‐term contracts have provided in the past. Given this self‐reinforcing process, it is likely that the LNG market will soon look nothing like it did as recently as a decade ago. Buyers and sellers will rely on shorter‐term contracts, and the longerterm contracts that do exist will be linked to spot LNG prices rather than crude oil. Consumers and producers will also benefit from more flexible pricing that more accurately reflects rapidly changing fundamentals of supply and demand.